Respuesta de la estructura zooplanctónica a cambios físicos y biológicos en una laguna pampásica (laguna Lacombe) - Ardohain, Diego Martin (2014)
The changes in zooplankton composition at Lacombe Lake during two annual cycles related to environmental (rainfall, hydrometric level, conductivity, transparency and nutrients) and biotic factors (phytoplankton palatability and presence of submerged macrophytes) were analyzed. The shallow lake showed alternating periods of turbid and clear water associated with phytoplankton density and occasional colonization of the lake by submerged macrophytes (Potamogeton pectinatus and Myriophyllum quitense). The MDS ordination analysis based on environmental data showed a clear separation of clear and turbid water periods but the division became more diffuse when the analysis performed was based on zooplankton species density. The results of SIMPER analysis indicated that the quality (palatable nanoplankton) and quantity of phytoplankton constituted the most important variable in both annual cycles for the period characterization, while pH, chlorophyll a and turbidity were relevant in 2001-2002 period, and hydrometric level, conductivity and transparency in 2005-2006. Some euplanktonic rotifers were relevant during turbid periods (Brachionus caudatus, B. havanaensis, Filinia longiseta, Keratella lenzi, K. tropica, Polyarthra vulgaris) whereas crustaceans achieved their maximum density during clear periods (Notodiaptomus incompositus, Microcyclops alius, Metacyclops mendocinus and Ceriodaphnia cfr. dubia). In both annual cycles, the zooplankton maintained similar composition in this seepage shallow lake in spite of the occurrence of contrasting environmental conditions.